ANXIETY STATUS OF PATIENTS AFTER COVID-19 TREATMENT AT AGRICULTURAL GENERAL HOSPITAL IN 2022 AND SOME RELATED FACTORS (Vietnam Journal of Community Medicine, 2024)
Background: Psychological effects (anxiety) are part of the post-COVID-19 syndrome. Thesesymptoms may persist from the initial illness or develop after recovery, affecting the patient’s abilityto perform daily activities.Objectives: Determining the anxiety status of patients after Covid-19 treatment at AgriculturalGeneral Hospital in 2022 and some related factors.Methods: Cross-sectional survey, quantitative research.Results: The study collected information from 400 patients after Covid-19 treatment at AgricultureGeneral Hospital through a questionnaire. The study results showed that the rate of patients feelinganxiety was 69,5%, of which 14,8% of patients with mild anxiety and 25,3% of patients with severeanxiety. The factor related to patient’s anxiety includes: education, employment, income, economicchange, living status, living with children under 18 years old, post-covid-19 infection, source ofCovid-19 infection, treatment level, comorbidities and hospital landscape (p
Keywords: Anxiety, Covid-19 patients, related factors.